2008
DOI: 10.1007/s00168-008-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental causes of inland–coastal income inequality in post-reform China

Abstract: This paper investigates the fundamental causes of the widening inland-coastal inequality in China during the reform period 1978-2004 within a systematic framework of economic development theory.We highlight the roles of three policy variables, namely globalization, decentralization and marketization, in determining the income gap between inland and coastal regions. The results derived from both time-series and panel data provide strong evidence that these policies are thus far inequality-enhancing. This findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 54 publications
(63 reference statements)
0
37
0
Order By: Relevance
“…3 Because this paper focuses only on mainland China we exclude the two special administrative regions of Hong Kong and Macao. Other empirical studies using provincial data for mainland China include Wu (2007), Fan and Sun (2008), Hao and Wei (2010), Lin et al (2013), Dreger and Zhang (2014), Yuan and Hamori (2014) and . 4 National Bureau of Statistics of the People's Republic of China website link is http://www.stats.gov.cn/english/.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…3 Because this paper focuses only on mainland China we exclude the two special administrative regions of Hong Kong and Macao. Other empirical studies using provincial data for mainland China include Wu (2007), Fan and Sun (2008), Hao and Wei (2010), Lin et al (2013), Dreger and Zhang (2014), Yuan and Hamori (2014) and . 4 National Bureau of Statistics of the People's Republic of China website link is http://www.stats.gov.cn/english/.…”
Section: Datamentioning
confidence: 99%
“…Privately-owned businesses increasingly replaced state-owned enterprises, foreign direct investment increased, and exports increased, notably with the accession of China into WTO membership (Tung, 2005;Wu, 2007). However, growth across regions of China has been uneven during the post-reform period (Wei, 2002;Fan and Sun, 2008;Hao and Wei, 2010;Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hao and Wei (2010), Jian et al (1996), Tsui (2007) and Ying (1999) are representative works establishing this notion using provincial GRP per capita data. In these studies it is found that inequality between the inland and coastal regions increased while that within the inland and coastal regions decreased over time.…”
Section: Inland and Coastal-level Decompositionmentioning
confidence: 99%
“…They also reached the same conclusion: that there was an increase in inequality between the inland and coastal regions. Hao and Wei (2010) considered GRP per worker and showed that inequality between the inland and coastal regions increased sharply during 1978-2004. They repeated their exercises by excluding the municipalities, and their findings remained the same.…”
Section: Inland and Coastal-level Decompositionmentioning
confidence: 99%